EFISIENSI PEMUPUKAN P PADA LAHAN SAWAH PASIR PANTAI SELATAN YOGYAKARTA YANG DIBERI ZEOLIT DENGAN INDIKATOR TANAMAN PADI (Oryza sativa L.) - Sri Hartati; Mulud Suhardjo; Catur Gunawan Podo Winarno (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2008)
Efficiency of P Fertilizer at Sandy Paddy Soil of South Yogyakarta That were Added Zeolite with Rice (Oryza sativa L.) as Plant Indicator. The aim of this research were to study the efficiency of P fertilizer at sandy paddy soil of South Yogyakarta that were added zeolite with rice as plant indicator and to know treatment combination which give the highest yield of rice plant (Oryza sativa L.). This research were conducted in February 2007 to June 2007at paddy soil in Siliran V, Karangsewu, Galur, Kulonprogo Daerah Istimewa Yogyakarta. This research are field experiment. The experiment design are used Split Plot Design, as a main plot was zeolit, i.e. no zeolit and 750 kg.ha‐1 zeolite. Sub plot consist of five levels of P fertilizer, i.e. 0, 50, 100, 150, 200 kg.ha‐1 SP36. Each treatment was three replicated so there is 30 treatment plot. Data analyzed with F test, Kruskal‐Wallis test, DMRT 5% and Correlation test. The result from this research shows that added 750 kg.ha‐1 zeolit are not significant for efficiency of P absorption and Agronomic Efficiency Index. The added of SP36 fertilizer has increased significant highly efficiency of P absorption on SP36 dosage 200 kg.ha‐1 is 168.49 or can increase 127.87% in comparison with control. Interaction between 750 kg.ha‐1 zeolit and SP36 dosage 100 kg.ha‐1 (Z1P2) has highly Agronomic Efficiency Index (234.3). Interaction between zeolit and P fertilizer has not significant increased rice yield, but treatment interaction between 750 kg.ha‐1 zeolit and SP36 dosage 100 kg.ha‐1 give the highest highly unhulled paddy crop (23.61 g.plant‐1) and the highest weight 1000 unhulled paddy crop (24.33 g). Keyword : P efficiency, zeolit, rice plant